Histopathological study for the effect of vitamin C on the some mice tissues treated with nitrate: R.N.Al-saadi ,E.H.Al-taae - Al-saadi, R. N. (The Iraqi Journal of Veterinary Medicine, 2007)
Thirty two mice were used to study the histopathological changes resultedfrom the effect of vitamin C on the some mice tissues treated with nitrate.Mice were divided randomly in to four equal groups. The 1st group was givenVit C and potassium nitrate via water. The 2nd group was given potassium nitrateand the 3rd group received Vit C only, while the 4th group represented thecontrol.Two animals from each group were scarified weekly. The results showedsimilar pathological changes in the 1st and 2nd group especially in the stomachand intestine which gave severe changes that characterized by hyperplasticchanges in addition for the hemorrhages and the infiltrations of inflammatorycells in all layers of both organs. Less alteration was seen in the liver andkidney. On the other hand, no pathological changes in the 3rd and 4th groupwere recorded